Kinerja Keuangan Industri Sepak Bola dalam Perspektif Likuditas dan Solvabilitas - Muhammad Alrezqi Ananda; Ashari Sofyaun; Matyani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
The purpose of this study is to determine the effect of Liquidity and Solvabilty on financial performance in the professional football industry. In this study, the number of samples was 11 football industries. The method used in this study is multiple regression analysis with secondary data taken from the financial reports of the football industry for the period 2020 to 2023. The results of the study indicate that partially the Current Ratio and Quick ratio variables have no effect. Debt to Asset Ratio and Debt to Equity Ratio are proven to have a statistically significant effect on Financial Performance with a negative relationship direction.